Neuroleptic Malignant Syndrome - review of pathophysiology, clinical presentation, differentiation and management - Strus, Karolina; Madera, Magdalena; Dąbrowska, Natalia; Mazur, Sylwia; Zdunek, Roksana; Mazur, Agata; Nagórska, Emilia; Marcinkowski, Krzysztof; Bizan, Aleksy; Kublińska, Aleksandra (Journal of Education, Health and Sport, 2024)
Introduction and purpose: The number of invented and produced medications has increased over recent years. Besides their positive impact on health, they invariably provide various kinds of side effects. This review is focused on malignant neuroleptic syndrome, a rare condition with no fully confirmed pathogenesis, which at least partially can be explained as an adverse effect of blocking dopamine receptors. Even though it usually affects psychiatric or neurological patients, doctors of all medical specializations should stay alert, as the condition can often lead to premature death. Brief description of knowledge: The main symptoms associated with NMS are hypertonia, hyperpyrexia, autonomic instability and altered consciousness. They can appear in any configuration, sometimes followed by less characteristic manifestations. It should be primarily differentiated from serotonin syndrome, malignant hyperpyrexia and catatonia, mostly through the interview of those who have taken medications and undergone surgeries, as there are not any specific lab tests available. Fundamental treatment methods consist of neuroleptic withdrawal, intensive supportive care, drug administration and eventually ECT. Summary: NMS is an uncommon, severe disease that should be carefully considered in patients treated with neuroleptics. Due to its rarity and sudden onset, it appears to be problematic to conduct widespread research and studies, so there are still no concrete, consistent and unquestioned guidelines on recognizing and treating the condition.